2017
DOI: 10.3389/fphys.2017.00494
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes: A Rising Star in Failing Hearts

Abstract: Although exosomes were previously recognized as a mechanism for discharging useless cellular components, growing evidence has elucidated their roles in conveying information between cells. They contribute to cell–cell communication by carrying nucleic acids, proteins and lipids that can, in turn, regulate behavior of the target cells. Recent research suggested that exosomes extensively participate in progression of diverse cardiovascular diseases (CVDs), such as myocardial infarction, cardiomyopathy, pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 193 publications
(231 reference statements)
0
52
0
Order By: Relevance
“…However, LEC treated with DM-Exos didn’t show any significant changes in wound healing rate compared to control, untreated wounded cells. Similar studies have previously explored the role of Exos in cell repair and wound healing in other cell types such as in skin 20 , 33 , 36 , 37 , skeletal 38 and cardiac 39 , 40 muscle. A very recent study has shown that Exos derived from human amniotic epithelial cells promoted wound healing and inhibited scar formation in skin 36 .…”
Section: Discussionmentioning
confidence: 76%
“…However, LEC treated with DM-Exos didn’t show any significant changes in wound healing rate compared to control, untreated wounded cells. Similar studies have previously explored the role of Exos in cell repair and wound healing in other cell types such as in skin 20 , 33 , 36 , 37 , skeletal 38 and cardiac 39 , 40 muscle. A very recent study has shown that Exos derived from human amniotic epithelial cells promoted wound healing and inhibited scar formation in skin 36 .…”
Section: Discussionmentioning
confidence: 76%
“…These exosomes are currently of major interest with respect to further elucidating cell-cell communication (e.g., Kruger et al, 2014). Specifically, communication through the content of exosomes is considered an important factor for orientation of cells (Xu et al, 2017). Several micro-RNAs, transcription factors and cytokines were identified to be involved in the transfer of epigenetic reprogramming of cells in order to direct them into a specific lineage differentiation.…”
Section: Regulation Of the Differentiation Of Stem Cells In A Living mentioning
confidence: 99%
“…The beneficial paracrine effects of transplanted MSCs are, in part, mediated by the release of exosomes. These are extracellular vesicles 30–100 nm in diameter, which contain a variety of molecules, including proteins, miRNA, and mRNA, and thereby play an important role in cell-cell communication [ 213 , 214 ]. Several preclinical studies have demonstrated the benefits of exosome administration in the treatment of CVDs.…”
Section: Strategies To Improve Mscsmentioning
confidence: 99%